2016
DOI: 10.4103/0259-1162.164732
|View full text |Cite
|
Sign up to set email alerts
|

Oral clonidine and gabapentin suppress pressor response: A prospective, randomized, double blind study

Abstract: Background:Pressor response is a part of stress response caused by reflex sympathetic discharge due to direct laryngoscopy and tracheal intubation resulting in tachycardia, hypertension and arrhythmias. Both clonidine, and gabapentin administered orally can effectively blunt this detrimental hemodynamic response.Aim:To study the effect of oral clonidine to blunt the pressor response to direct laryngoscopy and to compare it with oral gabapentin. To observe for postoperative sedation and side effects if any.Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
5
1
0
Order By: Relevance
“…On comparing patients in Group G with those in Group CL, sedation was statistically higher in Group G up to 16 hours compared to the CL group. Our results correlate with those of the study done by Kapse et al [ 10 ] in which patients had better sedation in the gabapentin group, which is due to the antagonism of NMDA receptors.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…On comparing patients in Group G with those in Group CL, sedation was statistically higher in Group G up to 16 hours compared to the CL group. Our results correlate with those of the study done by Kapse et al [ 10 ] in which patients had better sedation in the gabapentin group, which is due to the antagonism of NMDA receptors.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, patients in Group CL and Group G had a significant reduction in HR during pneumoperitoneum compared to patients in Group C. This significant reduction in HR is comparable to the findings of Kapse et al [ 5 ], Singhal et al [ 10 ], and Waikar et al [ 11 ], which showed a statistically significant reduction in HR in clonidine and gabapentin groups during endotracheal intubation and carbon dioxide insufflation. Clonidine, as an alpha-2 adrenergic agonist in the nucleus tractus solitarius (NTS), excites a pathway that inhibits excitatory cardiovascular neurons.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations